Students’ Perspective on the Use of TED-Ed Video on Enhancing English Comprehension - Anandha, Anandha; Dini Anggraheni, Dini Anggraheni; Yogatama, Adiprana (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
This study investigates the use of TED-Ed video as a learning strategy to improve the understanding of English among undergraduate students in the Economics Faculty at Universitas Semarang. The goal of this research is to assess the effectiveness of the TED-Ed video in assisting students in mastering the English language skills required to understand economic theory. The case study method is used to investigate the experiences of students when using video as a learning tool. Data is collected through pre-test & post-test, observation, and interviews. The results of the study showed that using TED-Ed Video can increase students' motivation and participation, improve their understanding of English, and provide practical context for implementing economic concepts. This study contributes to English language learning and economic education by demonstrating innovative techniques.